Quaternary Ammonium-Based Ionosilica Hydrogels as Draw Solutes in Forward Osmosis - Alysson Duarte Rodrigues; Matthieu Jacob; Véronique Gauchou; Jean-Olivier Durand; Philippe Trens; Peter Hesemann (Molecules, 2020)
In the last few years, forward osmosis (FO) has attracted increasing interest as a sustainable technique for water desalination and wastewater treatment. However, FO remains as an immature process principally due to the lack of efficient and easily recyclable draw solutes. In this work, we report that ionosilica hydrogels based on quaternary ammonium halide ionosilica are efficient draw solutes in FO. Fluidic ionosilica hydrogels were obtained via hydrolysis-polycondensation reactions of a trisilylated quaternary ammonium precursor in slightly acidic water/ethanol solvent mixtures. The liquid-to-gel transition of the precursor and the kinetics of the formation of hydrogels were monitored by liquid NMR measurements. The formed hydrogels were shown to generate osmotic pressure up to 10.0 atm, indicating the potential of these hydrogels as efficient draw solutes in FO. Our results suggest that iodide anions are the osmotically active species in the system. Regeneration of the hydrogels via ultrafiltration (UF) was successfully achieved, allowing the development of a closed FO-UF process. However, the osmotic performances of the ionosilica hydrogels irreversibly decreased along the successive FO-UF cycles, probably due to anion exchange processes.